The echoes of the outside world events on the pages of the Chronicle of Zofia Grothówna in years 1703-1741 - Mierzejewska, Milena (Saeculum Christianum. Pismo Historyczne, 2021)
The article describes the echoes of the events from the outside world in an enclosed Norbertine convent in Imbramowice and is mainly based on the records taken from The Chronicle of Sophia Grothówna from the years 1703-1741. Although the Norbertine monastery was (and still is) enclosed, it maintained communications with the outside world on a regular basis but unwillingly. This article discusses just such situations. Sisters had to contend with numerous military invasions, requesting ever larger contributions and looting the surroundings belonging to the nuns’ granges. During the wars of the seventeenth century a number of epidemics broke out, which reached the surrounding areas in Imbarmowice. The peasants contracted the plague from the army. Other events included the outbreak of fires, the largest of which broke out in 1704 and as a result many sisters had to leave the monastery and move to other monasteries or return to their homes. The reconstruction of the monastery took almost 20 years. The article describes information about the floods, strong gales, hunger, cold and drought that ravaged the monastery and caused major damage in the convent farms.